An Empirical Study of Educational Inequalities in Rural and Urban Areas of Pakistan - Ayjaz Ahmed; Hira Mujahid (Institute of Business Management, 2021)
The central object of this paper is to give detailed analysis of educational disparity in Pakistan. This study is examined all over provinces of rural and urban of Pakistan including Islamabad for the period of 2014-15 and the data is used from PSLM. In particular, we calculate education inequality all over the population and beyond the employed population. This study is investigated individually male and female having age equal to 15 years and over and are not being enrolled in any educational institutions. The study finds that there is lack of education over the populace. Whereas, strength of education disparity is extremely low athwart in employed people. When we compare rural-urban areas of Pakistan. The study find that urban areas are less disparity in education as compare to rustic areas. The study also investigates that education inequality are extra serious amid female than male. The province wise contrast shows that education inequality is high in Baluchistan and Sindh while there is less education disparity is Islamabad.